DAS GARANTIAS CONSTITUCIONAIS E O DEVIDO PROCESSO NO ESTADO LIBERAL AOS DIREITOS FUNDAMENTAIS E O PROCESSO JUSTO NO ESTADO DEMOCRÁTICO DE DIREITO - Costa, Miguel do Nascimento (Revista da AJURIS - Qualis A2, 2016)
CONSTITUTIONAL GUARANTEES AND DUE PROCESS IN THE LIBERAL STATE FUNDAMENTAL RIGHTS AND FAIR TRIAL IN THE DEMOCRATIC STATE OF LAW RESUMO: Este ensaio tem por escopo analisar as premissas conceituais mínimas do devido processo legal, a partir da análise das garantias constitucionais estabelecidas no Estado Liberal, assim como do processo justo, do ponto de vista dos direitos fundamentais no Estado Democrático de Direito. PALAVRAS-CHAVE: devido processo legal; garantias constitucionais; estado liberal; processo justo; direitos fundamentais; estado democrático de direito. ABSTRACT: The present assay has for target to analyze the minimum conceptual premises of due process of law, from the analysis of the guarantees constitutional in the Liberal State, thus with of the process just, from the perspective of the basic rights in the Democratic State of Right. KEYWORDS: due process of law; guarantees constitutional; liberal state; process just; right basic; democratic state of right. SUMÁRIO: Introdução; 1 Estado Liberal clássico e as suas características jurídicas essenciais; 2 Do devido processo legal no Estado Liberal; 3 Do Estado Social ao Estado Democrático de Direito e as suas características jurídicas essenciais; 4 O processo justo no Estado Democrático de Direito; 5 O direito ao processo justo na concepção do novo Código de Processo Civil brasileiro (Lei nº 13.105/2015); Apontamentos conclusivos; Referências. SUMMARY: Introduction; 1 Liberal State classic and essential legal characteristics; 2 The due process of law in the liberal state; 3 The Social State to the Democratic State of Law and its essential legal characteristics; 4 The right to due process in the Democratic State of Law; 5 The right to due process in the design of the project of the new Code of Civil Procedure (Law nº 13.105/2015); Conclusive notes; References.